Autoantibody Profiles in Collagen Disease Patients with Interstitial Lung Disease (ILD): Antibodies to Major Histocompatibility Complex Class l-Related Chain a (MICA) as Markers of ILD. Issue 10 (January 2015) - Furukawa, Hiroshi; Oka, Shomi; Shimada, Kota; Masuo, Kiyoe; Nakajima, Fumiaki; Funano, Shunichi; Tanaka, Yuki; Komiya, Akiko; Fukui, Naoshi; Sawasaki, Tatsuya; Tadokoro, Kenji; Nose, Masato; et al.
Interstitial lung disease (ILD) is frequently associated with collagen disease. It is then designated as collagen vascular disease-associated ILD (CVD-ILD), and influences patients' prognosis. The prognosis of acute-onset diffuse ILD (AoDILD) occurring in patients with collagen disease is quite poor. Here, we report our investigation of auto-antibody (Ab) profiles to determine whether they maybe useful in diagnosing CVD-ILD or AoDILD in collagen disease. Auto-Ab profiles were analyzed using the Lambda Array Beads Multi-Analyte System, granulocyte immunofluorescence test, ProtoArray Human Protein Microarray, AlphaScreen assay, and glutathione S-transferase capture enzyme-linked immunosorbent assay in 34 patients with rheumatoid arthritis (RA) with or without CVD-ILD and in 15 patients with collagen disease with AoDILD. The average anti-major histocompatibility complex class I-related chain A (MICA) Ab levels were higher in RA patients with CVD-ILD than in those without (P = 0.0013). The ratio of the average anti-MICA Ab level to the average anti-human leukocyte antigen class I Ab level (ie, MICA/Class I) was significantly higher in RA patients with CVD-ILD compared with those without (P = 4.47 × 10 –5 ). To the best of our knowledge, this is the first report of auto-Ab profiles in CVD-ILD. The MICA/ Class I ratio could be a better marker for diagnosing CVD-ILD than KL-6 (Krebs von den lungen-6).